Pharmacokinetics, Safety and Efficacy of Intravenous Vedolizumab in Paediatric Patients with Ulcerative Colitis or Crohn's Disease: Results from the Phase 2 HUBBLE Study. (17th March 2022) - Hyams, Jeffrey S; Turner, Dan; Cohen, Stanley A; Szakos, Erzsébet; Kowalska-Duplaga, Kinga; Ruemmele, Frank; Croft, Nicholas M; Korczowski, Bartosz; Lawrence, Promise; Bhatia, Siddharth; Kadali, Harisha; Chen, Chunlin; et al.
Abstract: Background and Aims: To date, there are no systematic pharmacokinetic [PK] data on vedolizumab in paediatric inflammatory bowel disease [IBD]. We report results from HUBBLE, a dose-ranging, phase 2 trial evaluating the PK, safety and efficacy of intravenous vedolizumab for paediatric IBD. Methods: Enrolled patients [aged 2–17 years] with moderate to severe ulcerative colitis [UC] or Crohn's disease [CD] and body weight ≥10 kg were randomized by weight to receive low- or high-dose vedolizumab [≥30 kg, 150 or 300 mg; <30 kg, 100 or 200 mg] on Day 1 and Weeks 2, 6 and 14. Week 14 assessments included PK, clinical response and exposure–response relationship. Safety and immunogenicity were assessed. Results: Randomized patients weighing ≥30 kg [UC, n = 25; CD, n = 24] and <30 kg [UC, n = 19; CD, n = 21] had a baseline mean [standard deviation] age of 13.5 [2.5] and 7.6 [3.2] years, respectively. In almost all indication and weight groups, area under the concentration curve and average concentration increased ~2-fold from low to high dose; the trough concentration was higher in each high-dose arm compared with the low-dose arms. At Week 14, clinical response occurred in 40.0–69.2% of patients with UC and 33.3–63.6% with CD in both weight groups. Clinical responders with UC generally had higher trough concentration vs non-responders, while this trend was not observed in CD. Fourteen per cent [12/88] of patients had treatment-related adverse events and 6.8% [6/88] had anti-drug antibodies. Conclusions: Vedolizumab exposure increased in an approximate dose-proportional manner. No clear dose–response relationship was observed in this limited cohort. No new safety signals were identified. Graphical Abstract: